Regression analysis unified concepts, practical applications, and computer implementation - Bowerman, Bruce L.; O'Connell, Richard T.; Murphree, Emily S. (New York, N.Y. Business Expert Press, 2015)
Concise and innovative book that gives a complete presentation of applied regression analysis in approximately one-half the space of competing books. With only the modest prerequisite of a basic (non-calculus) statistics course, this text is appropriate for the widest possible audience.
Preface -- 1. An introduction to regression analysis -- 2. Simple and multiple regression: an integrated approach -- 3. More advanced regression models -- 4. Model building and model diagnostics -- Appendix A. Statistical tables -- References -- Index.
Dr. Mary Gretchen F. Chaves (Recommending faculty) : Management Cluster
Includes bibliographical references (page [261]) and index.
Keywords: Regression analysis